Study design and baseline characteristics for the reflect gene therapy trial ofm.11778g>A/ND4-LHON. Issue 1 (15th November 2022) - Subramanian, Prem S; Newman, Nancy J; Moster, Mark; Wang, An-Guor; Yu-Wai-Man, Patrick; Donahue, Sean; Leroy, Bart P; Carelli, Valerio; Biousse, Valerie; Vignal-Clermont, Catherine; Sergott, Robert C; Sadun, Alfredo A; et al.
Abstract : Objective: REFLECT is the first randomised, double-masked, placebo-controlled multicentre phase 3 clinical trial that evaluated the efficacy and safety of bilateral intravitreal (IVT) injection of lenadogene nolparvovec in subjects with Leber hereditary optic neuropathy carrying the m.11778G>A mutation. Methods and analysis: A total of 98 subjects were enrolled with vision loss of ≤12 months. The subjects were randomised to one of two treatment arms with all subjects receiving an intravitreal (IVT) injection of lenadogene nolparvovec in their first affected eye and the second-affected eye randomised to receive IVT of either lenadogene nolparvovec or placebo. Results: The majority of subjects were male with a mean duration of vision loss of 8.3 months. All but one subject experienced bilateral loss of vision at the time of injection. The mean best-corrected visual acuity of first-affected eyes was worse compared with second/not-yet-affected eyes. Analysis of retinal anatomical parameters showed increased thinning in the first-affected eyes when compared with the second/not-yet-affected eyes with both treatment arms showing significant changes compared with unaffected individuals. Conclusion: The REFLECT trial is the third and the largest phase 3 clinical study evaluating lenadogene nolparvovec in m.11778G>A Leber hereditary optic neuropathy (LHON) subjects. The observed demographics in REFLECT are consistent with previous reports in LHON subjects in the acute and dynamic phases of LHON disease. Combined with the visual function and anatomical parameters obtained in the previous RESCUE and REVERSE trials, REFLECT has provided a uniformly collected data set that should help direct future LHON clinical trials.